Inovação, sustentabilidade e desempenho econômico-financeiro: uma análise das empresas persistentemente listadas no prêmio Valor Inovação Brasil e no ISE - Gurgel, Danielle Maria Porto (2021)
There is a growing demand for innovative organizations that are aligned with sustainability and that, in addition to seeking profitability, present effective actions related to environmental and social issues. In this context, in the light of the Theory of Resource Based Vision (RBV), innovation and sustainability are approached as antecedents of obtaining competitive advantages, which is represented by the economic-financial performance of organizations. In this perspective, this research aims to investigate whether the companies recognized as innovative and sustainable, listed in the Valor Inovação Brasil Award, and in the Corporate Sustainability Index (ISE), persistently present different economic and financial performance from the other companies listed in the Valor Award Innovation Brazil. For the purpose of this study, the companies that participated in at least two years in the ranking of the Valor Inovação Brasil Award and the ISE between 2016 and 2019 are considered persistent. The sample was composed of 43 publicly traded companies, listed Valor Inovação Brasil Award in the years 2016 to 2019, which released its financial statements at B3. Statistical techniques were used, such as the Mann-Whitney test and test of the stations with Wilcoxon signs. The results showed that organizations recognized as persistent innovative and sustainable have better economic-financial performance than those organizations that are only innovative in a non-persistent way, this performance being demonstrated by the LPA, ROE, ROA and Net Margin indicators. For the group of EBITDA indicators, % Conversion of EBITDA into FCO and Current Liquidity, it was not statistically verified that companies persistent in innovation and sustainability have better indicators than non-persistent ones.